Applied of CCME Water Quality Index for Protection of Aquatic Life in the Tigris River within Baghdad city. - Al-Janabi, Zahraa Zahraw; Al-Obaidy, Abdul-Hameed M Jawad; Al-Kubaisi, Abdul-Rahman (Al-Nahrain Journal of Science, 2018)
In the present study, Tigris River within Baghdad city was monitored for a variety of physical and chemical parameters to determine water quality during 2010. Water quality indices (WQIs) were calculated for protection of aquatic life, using the model of CCME WQI (Canadian Council of Ministers of the Environment Water Quality Index). Twelve parameters were selected namely: Lead, Iron, Zinc, Manganese, Turbidity, pH value, Dissolved Oxygen, Water Temperature, Phosphate, Ammonia, Nitrate and Nitrite. The results revealed that station 3 which was located in south of Baghdad was more polluted than the other stations. The WQI ranking was between marginal in station 1, 2 to poor in station 3. The highest deviation occurred in lead, Iron and Turbidity, this parameter made a big contribution in decreasing the value of WQI.